Social responsibility: theoretical-methodological aspect - Андрющенко, А. І.; Вітковська, І. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article is devoted to the actual one of issues of forming the legal, social state, democratic society, namely to formation and development of social responsibility of the state, business and civil society. In the article social responsibility is examined as relatively independent type of responsibility within the framework of sociological approach.